Dental Hygienist Students' Learning About Motivational Interviewing - Ann-Christin Johansson; Gunnar Johannsen; Lars Uhlin; Annsofi Johannsen (MDPI AG, 2014)
Objective: To investigate whether dental hygienist students through peer-learning can increase their ability to conduct motivational interviewing (MI) compared with students who follow the regular curriculum. The aim was also to get an insight into the process of learning of MI. Materials and Methods: Ten dental hygienist students were randomly selected to either the intervention group (IG) or the control group (CG). Students in the IG performed two MI sessions, which were discussed in a peer group and with a tutor. Thereafter the students performed the third MI sessions, which was evaluated by "Motivational Interviewing Treatment Integrity Code, Version 3.1". The CG consisted of five students who followed the regular curriculum in the education and they conducted one MI session. A questionnaire was used to study how students reflected before and after these MI sessions. The analysis was performed by using descriptive statistics and for the comparison between groups the Mann-Whitney test was used. Results: The students in the IG used significantly more, simple and complex reflections (p < 0.05) compared to the CG. The IG gave also significantly less information during the counseling, and thereby asked more open-ended questions than the CG (p < 0.05). Both groups planned their MI sessions carefully by preparing questions before they met the patients. Conclusion: Dental hygienist students in the present study increased their skills in motivational interviewing by peer-learning from other students and from a tutor, compared to a control group.